Pendekatan Culturally Responsive Teaching Menggunakan Media Canva pada Pembelajaran Bahasa Indonesia di SMA - Winda NurIsmani; Imas Juidah; Agus Nasihin; Yayah Kurniah (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2025)
This study examines the integration of Culturally Responsive Teaching (CRT) with Canva in Indonesian language learning at the senior high school level. Using a qualitative case study at SMA Negeri 2 Indramayu, data were gathered through observations, interviews, and student work analysis. The results show that most students (83%) effectively used Canva to create culturally themed concept maps and texts, demonstrating increased engagement, creativity, and cultural understanding. The study concludes that combining CRT with digital media enhances meaningful learning by connecting students’ cultural identities with academic content. This approach offers a relevant model for inclusive and contextualized language instruction in Indonesian schools.